Major blunt trauma causes increased mortality up to 12 years: Long-term survival in 3 557 patients compared to 35 502 control persons. Issue 11 (November 2020) - Kuorikoski, Joonas; Brinck, Tuomas; Willa, Kirsi; Heinänen, Mikko; Handolin, Lauri; Söderlund, Tim
Highlights: Major blunt trauma patients have increased long-term mortality compared to controls. The difference in mortality remains, even with patients surviving at least one year post-trauma. According to our results the short-term mortality is insufficient measure for outcome in major trauma patients as trauma causes increased mortality at least up to 12 years post-trauma. Our findings suggest that age, male gender, long-term unemployment, ASA grade, head AIS 5-6 and transfer to another facility ICU/HDU are associated with increased and full insurance coverage for decreased long-term mortality. Abstract: Background: Trauma registries usually report 30-day or in-hospital mortality as an outcome measure. However, some studies criticize this measure as inadequate; the impact of a major trauma could last longer than 1 month after the injury. We studied the long-term mortality of patients who sustained a major trauma. Methods: The Helsinki University Hospital's trauma registry was used for patient identification from 2006 to 2015 (New Injury Severity Score ≥ 16 and blunt mechanism of injury). For each trauma registry patient, 10 control persons matched by age, sex, and county of residency were obtained from the Population Register Center of Finland. Cause of death information was obtained from Statistics Finland. Results: We included 3 557 trauma registry patients and 35 502 control persons. Follow-up ranged from 1 year 7 months to 11 years 7 months. The 1-year mortality was 11 times higher in the trauma-patient group (22% vs. 2%). The long-term (approximately 12 years) mortality after the injury was 2.6 times higher in the trauma-patient group (46% vs. 18%). For patients surviving at least 1 year post-trauma, the mortality at 12 years was 2.2 times higher than in the control group (31% vs. 14 %). The cause of death was a disease in 73.3% of the trauma patients and 93.6% of the controls. Accidents were more often a cause of death in the patient population than in the control population (21.2% vs. 4.1%). Suicide was the cause of death in 3.0% of patients and 1.1% in controls. Several factors associated with increased mortality were identified. Conclusions: Major trauma patients had significantly higher long-term mortality compared to controls. To the best of our knowledge, this is the first study on this subject with a follow up of this duration with patients this severely injured and a cohort this large.